PENGARUH PENGENDALIAN PERSEDIAAN KANTONG PUPUK TERHADAP KELANCARAN PROSES PRODUKSI PUPUK NPK DI PT. PUPUK SRIWIDJAJA PALEMBANG - Rifani Akbar Sulbahri; Armedi Azhari (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
Inventory is one of the elements of current assets and is the largest and most active element in the company's operations. In the case of inventory procurement, companies usually make purchases in large numbers. Control of a company will experience changes. Therefore, it is necessary and assessment of each transaction. Based on the results of the study, it can be concluded that the control Based on the results of data analysis the effect of the supply of fertilizer bag control on the smooth process of NPK fertilizer production in the company PT. Pusri Palembang for 2016-2017 period, the conclusions can be obtained as follows: Control of fertilizer bag inventory has an effect on the smooth production of NPK bag pupk in the company PT. Pusri Palembang for the 2016-2017 period. The results of the hypothesis test indicate that the tcount is greater than t table, which is 64.297> 2.032 and the significance value (sig.) 0.000 <0.05. Then it can be concluded that Ho is rejected and Ha is accepted, which means that the supply control of fertilizer bags (X) influences the smooth process of NPK fertilizer production (Y). Then, the regression coefficient of bag fertilizer supply control (X) on the smooth production process (Y) is 350,243 in a positive direction. This shows that the control of fertilizer bag stock has increased by 1 point, so the smooth process of NPK fertilizer production will increase by 350,243. This means that the higher the supply of fertilizer bags, the higher the smooth process of NPK bag production. Keywords: Control of Fertilizer Bag Inventory and Smooth Process of NPK Fertilizer Production